Patterns and cultural traditions of marriage among Khanabadosh of Mardan - Liaqat Ali; Mohammad Taieb (The Journal of Humanities & Social Sciences, 2022)
The purpose of the paper is descriptive analysis of the patterns and cultural traditions related to marriage of khanabadoshi community located in District Mardan of Khyber Pakhtunkhwa province of Pakistan. Data for this qualitative micro-focused research was collected through participant observation, key informants, in-depth interviews, and group discussions. A socio-economic survey of the total 90 households was conducted and found that majority of these inhabitants were having nuclear family system. It was noted that Khanabadosh of the reported area are going through a transitional period of spatial mobility towards permanent settlement and few of them have been settled as permanent residents in the area. Therefore, based on residence patterns, they were bifurcated into permanently settled and spatially mobile population. Majority of them were monogamous and prefer early marriages. Elopement is quite common among them. Those who are permanently settled, practice endogamous and exogamous marriages within themselves and with the host community respectively while those who are mobile are strictly endogamous. In monetary sense marriages are classified into marriage by bride-wealth (tak) and marriage by women exchange (badal). Permanently settled population prefers bride-wealth while spatially mobile practices exchange marriages. Divorce is commonly observed among them.